Design and tests of a rotary plug seedling pick-up mechanism for vegetable automatic transplanter - Ye, Bingliang; Zeng, Gongjun; Deng, Bin; Yang, Chiulan; Liu, Jikun; Yu, Gaohong (International Journal of Agricultural and Biological Engineering, 2020)
The rotary plug seedling pick-up mechanism for vegetable automatic transplanter is the technical bottleneck to improve the mechanization level of vegetable planting in China. In order to solve the problems of rotary seedling pick-up mechanism proposed in previous study, such as low success ratio of seedling pick-up at high speed, and interference between the seedling bowl and the end of the other seedling pick-up arm, a novel kind of rotary seedling pick-up mechanism of planetary gear train with combined type gears of incomplete denatured-eccentric-circular and non-circular gears was proposed. Through kinematic analysis of the seedling pick-up mechanism, the kinematics model was established. The computer-aided analysis and optimization software with human-computer interaction method was developed to realize parameters optimization of the seedling pick-up mechanism. Three-dimensional parametric design system of seedling pick-up mechanisms with combined non-circular gear transmission was developed for mechanism virtual simulation to verify the correctness of theoretical model and design results of the mechanism. The physical prototype of the mechanism was manufactured, and high-speed camera kinematics tests of the mechanism were conducted in the laboratory to study its kinematic characteristics. Laboratory seedling pick-up tests were carried out. The mechanism has the success ratio of seedling pick-up 96.3% without interference during seedling transporting when the rotation speed of the mechanism is 50 r/min and the seedling transplanting efficiency is 100 plants/min per row, showing that the novel mechanism has better working performance than the original one and could be applied in vegetable plug seedling transplanter.Keywords: vegetable automatic transplanter, rotary seedling pick-up mechanism, incomplete denatured-eccentric-circular gear, kinematic analysis, parametric designDOI: 10.25165/j.ijabe.20201303.5647Citation: Ye B L, Zeng G J, Deng B, Yang C L, Liu J K, Yu G H. Design and tests of a rotary plug seedling pick-up mechanism for vegetable automatic transplanter. Int J Agric & Biol Eng, 2020; 13(3): 70–78.